2021
DOI: 10.3389/fmars.2021.671024
|View full text |Cite
|
Sign up to set email alerts
|

Flow of Economic Benefits From Coral Reefs in a Multi-Use Caribbean Marine Protected Area Using Network Theory

Abstract: Adaptation to changes in the delivery of ecosystem services while maintaining resilience of natural systems is one of the main challenges faced by multi-use marine protected areas (MPAs). To overcome this, it is crucial to improve our understanding of interdependencies among resource users and ecosystems. In this study we used networks to model the socio-ecological system of a multi-use MPA in the southern Caribbean. Using a mixed-method approach, we built a socio ecological network (SEN) from the flow of econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Overall local and anthropogenic threats might be minimized due to limited access to the area, its MPA status, and low human populations. However, the latest evidence of the MPA's degradation due to parrotfish and other herbivores overfishing, changes in governance, and inadequate surveillance and law enforcement poses an imminent threat (Croquer et al 2016;Agudo-Adriani et al 2019;Cavada-Blanco et al 2020;Cavada-Blanco et al 2021). Thus, we suggest the urgent need to revise the MPA´s zoning and regulations, established in 1991, to protect these dense and extensive patches of Acropora cervicornis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Overall local and anthropogenic threats might be minimized due to limited access to the area, its MPA status, and low human populations. However, the latest evidence of the MPA's degradation due to parrotfish and other herbivores overfishing, changes in governance, and inadequate surveillance and law enforcement poses an imminent threat (Croquer et al 2016;Agudo-Adriani et al 2019;Cavada-Blanco et al 2020;Cavada-Blanco et al 2021). Thus, we suggest the urgent need to revise the MPA´s zoning and regulations, established in 1991, to protect these dense and extensive patches of Acropora cervicornis.…”
Section: Discussionmentioning
confidence: 93%
“…Different studies have shown that Los Roques harbours healthy populations of other key and vulnerable scleractinian species such as Acropora palmata and Dendrogyra cylindrus (Zubillaga et al 2005;Croquer et al 2016;Cavada-Blanco et al 2020;Cavada-Blanco et al 2021). Most likely because the archipelago remains outside the main impact route of hurricanes and has not been subjected to coastal development (Zubillaga et al 2005;).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the nature of the GMMTP as a multi-user MPA, the interdependencies between the coral reef ecosystem and the resource users could unravel potential adaptation challenges to the community under fluctuating ES conditions [17,18]. Due to events such as the Lombok Major Earthquake in 2018 and the COVID-19 pandemic in 2020, the GMMTP community has undergone profound lifestyle alterations, which were later reflected in their interactions with ES provisions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to events such as the Lombok Major Earthquake in 2018 and the COVID-19 pandemic in 2020, the GMMTP community has undergone profound lifestyle alterations, which were later reflected in their interactions with ES provisions. A follow-up assessment of coral reef services must be conducted to maintain ecological and social resilience as the implied goal under MPA establishment [9,18]. Some critiques stated that ES assessment often lacks insight into the social dimension, resulting in an incomplete portrayal of ES values.…”
Section: Introductionmentioning
confidence: 99%